Principles in practice? A policy review of the IOC's environmental sustainability agenda - Cain, Alison; Callan, Michael (Frontiers in Sports and Active Living, 2025)
This paper is a policy review focused on the environmental sustainability (ES) agenda of the International Olympic Committee (IOC). This incorporates exploration of IOC documents such as policies, strategies, guidelines, reports, codes, and conference outputs. The IOC's ES agenda is interpreted as both strategy around ES, as a plan of action to achieve desired outcomes, and policies around ES, as matters of practice and principle to be enacted. This review encompasses each of the IOC's three spheres of activity (as an organisation, as owner of the Olympic Games, and as leader of the Olympic Movement). The documentary analysis incorporates inductive thematic analysis and Critical Policy Discourse Analysis (CPDA). This allows for consideration of the role of the IOC as a driver of ES with the power and reach to influence pro-environmental behaviours on a global scale, as well as analysis of the extent to which documentary discourse demonstrates committed leadership in this sphere. Key themes arising from the data are networks and knowledge transfer, leadership and influence, governance and accountability, and opportunities and obstacles. Power relationships between stakeholders are important in terms of facilitating or inhibiting ES, and there are missed opportunities for the IOC both to better demonstrate positive ES outcomes from existing practices and to utilise its power in leveraging ES commitments from stakeholders across the Olympic Movement (OM). The application of CPDA highlights varying levels of commitment across these themes as well as a tendency toward ambiguity and contradiction that engenders the likelihood of unintended consequences including greenwashing. The IOC ES agenda needs to encompass clear and unambiguous policy and strategy with more explicit commitment and accountability across its three spheres of activity.